Development of Pedagogical Culture and Competence of Future Physical Culture Specialists in Higher Educational Institutions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In the article, the development of pedagogical culture and competence of future physical culture specialists in higher educational institutions, exercise. Through national action games, comprehensive information on the improvement of pedagogical culture, pedagogical research, medical examinations and methods of information supply were used.